PRDM16 regulates γδT17 cell differentiation via controlling type 17 program and lipid-dependent cell fitness - Nah, Jinwoo; Lee, Youngjin; Seong, Rho H. (Frontiers in Immunology, 2024)
γδT17 cells are a subset of γδT cells producing IL-17, which is crucial for protection against bacterial and fungal infections. It has recently been shown that γδT17 cells have enriched lipid storage and lipid metabolism. However, the regulation of γδT17 cell function and differentiation with respect to lipids remains unknown. Here, we report that PRDM16 is a critical regulator of γδT17 cell differentiation, controlling type 17 immunity gene expression program and lipid-dependent cell fitness. We demonstrated that γδT17 cells have higher lipid-dependent cell fitness, which is negatively correlated with the expression of Prdm16. Loss of Prdm16 enhances the function and differentiation of γδT17 cells, and increases their fitness in lipid-rich environments. Specifically, loss of Prdm16 exacerbates development of psoriasis in the skin, a lipid-rich organ, and Prdm16 controls lipid-mediated differentiation of Vγ4 + γδT17 cells, which are the major source of IL-17 during the onset of psoriasis. Our study highlights the potential impact of PRDM16 on lipid-dependent fitness and protective immune function of γδT cells and also on the immunotherapy of psoriasis and inflammatory diseases.